"A prison within a prison"? Examining the enfolding spatialities of care and control in the Barlinnie Special Unit. Issue 2 (7th May 2018) - McGeachan, Cheryl
Abstract : This paper uses one of Scotland's most controversial experiments in penal reform – the Barlinnie Special Unit – to examine the enfolding nature of care and control in carceral space. Connecting with recent arguments relating to "caring architecture" and using the framework of historical carceral geographies, it showcases the spatial complexities of implementing caring practices alongside reforming tactics. Beginning with a discussion of the care and control nexus within institutional spaces and its historical legacy, it considers the use of small units within the Scottish Prison System. Using the Barlinnie Special Unit as a pivot, the paper opens up the complex spatial arrangements and spatial tactics of experimental prison reform. It first examines the spatial and architectural dimensions of the Special Unit. Second, the paper focuses on issues of routine and inhabitation and the emotional uncertainty this generated for prisoners. Overall, this paper seeks to argue the importance of examining experimental spatial practices in prison reform history to highlight the interwoven spatialities of care and control in every‐day institutional life.